LH and FSH concentration and follicular development in Nellore heifers submitted to fixed-time artificial insemination protocols with different progesterone concentrations - Cipriano, R. S. [UNESP]; Carvalho, B. A. [UNESP]; Marangoni, N. R. [UNESP]; Nogueira, Guilherme de Paula [UNESP] (Elsevier B.V., 2011)
Nine heifers were pre-synchronized (PGF2 alpha, 12 days) and assigned into three groups with 6 repetitions each: (1) CL (similar to 8 days old, n = 13); (2) DIB + CL (n = 18); (3) DIB + EB (150 mu g of PGF2 alpha and 2 mg estradiol benzoate, n = 18). After progesterone (P4) device removal (8 days) and/or final PGF2 alpha, heifers were injected with either GnRH or EB in a 3 x 2 factorial totalling 49 observations (5 were excluded). The blood sampling schedule: every 12 h during P4 period; for LH pulse frequency on Days 3-5, every 15 min for 6 h during P4 period; after P4 removal and EB treatment, samples were collected every 3 h for 24 h or after GnRH every ill for 10 h. Ovarian follicle number and diameter were evaluated by ultrasonography every 12 h until the last blood sample and then 24h and 48 h later. After device insertion (12 h), the DIB + CL group had a lesser LH concentration than the DIB + EB group. After 36h, all DIB + CL-treated heifers had less LH than CL-heifers, and after 60 h, the DIB + EB group had less LH than the CL-group. Considering all P4 groups combined, LH peak amplitude was greater after GnRH compared to EB treatment but total area of LH peak amplitude and time to first peak was less. The CL-group had fewer follicles and a greater largest follicle diameter than DIB + CL and DIB + EB groups. When treated with EB, the DIB + CL group had a lesser ovulation rate at 24h than the CL- and DIB + EB-groups. Fixed time artificial insemination (FTAI) protocols promoted a pre-ovulatory LH peak, independent of previous exposure to the DIB coupled with a CL or not. The progesterone excess interfered with FSH and LH secretion, follicular development and ovulation within 24 h. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Progesterone; Bos indicus; Estradiol benzoate; GnRH; Ovulation